POTENSI PESERTA DIDIK TIPE QUITTER MENYELESAIKAN SOAL OPEN-ENDED MATERI SEGIEMPAT DAN SEGITIGA - Natalia Natalia; Sugiatno Sugiatno; Silvia Sayu (Jurnal AlphaEuclidEdu, 2021)
This study aims to determine the potential description of quitter type students in solving an open-ended question in the material of Quadrilateral and Triangle at SMP Negeri 20 Pontianak. The research method used is a descriptive method with a qualitative approach and a case study research form. The number of subjects in this study was 27 students of class VIII F SMP Negeri 20 Pontianak. The data collection tool used was the Adversity Response Profile (ARP) to get quitter type subjects, open-ended test questions, and interview guides with the help of teaching aids to probe deeper into the potential of quitter-type students. The results of the research on the written test showed that the potential of 2 quitter subjects in solving open-ended questions was still low with a percentage of only 22.22%. However, when interviewed with the help of teaching aids, additional information was obtained that the two quitter subjects showed better potential in solving open-ended questions and were able to provide more than one solution and more than one correct answer.